Collaborative learning as a tool in the teaching of Human Anatomy (Research, Society and Development, 2021)
Anatomical knowledge is essential for health professionals, although this discipline presents low performances in relation to the teaching and learning process. Thus, this research aimed to propose the use of collaborative learning as a tool to aid anatomy learning. The method was applied in the form of monitoring for students of the Nutrition and Nursing courses at the Federal University of Tocantins (UFT), campus of Palmas-TO. The students were divided into two groups, A and B, one group was responsible for addressing the theoretical content and the other for explaining and conducting the practical content, with rotation of these assignments. The effectiveness of the method was assessed by means of a questionnaire that used the Likert scale and analysis of the students' performance, through the notes diary of the discipline. To synthesize the results, the Tukey test was applied. It was observed that 95% of the participants after participating in the methodology stated that they had obtained a positive evolution in relation to the learning of human anatomy and recommended the application of the method in other disciplines. As the group of students participating in the collaborative methodology presented results above the average and the group of non-participating students, with HSD (Honestly Significant Difference) of 5%. In view of the great challenges faced in the teaching of anatomy, the encouragement to perform monitoring in a collaborative way can be a tool to assist in teaching strategies.